THE THEORETICAL AND METHODOLOGICAL APPROACHES TO CERTAIN POLITICAL PHENOMENON - THE "EXTREMISM - Alexander Aleksandrovich Pokhilko (Современная наука и инновации)
The article analyzes the processes of globalization, the uneven development of the Middle East, which as a consequence, lead to the marginalization of a large number of social strata of society in the Middle East and contribute to the creation of extremist movements and organizations.